Effect of albumen width, albumen height, and albumen index on haugh unit of sentul chicken eggs - Adji Nusa Bakti; Dedi Rahmat; Primiani Edianingsih (Jurnal Produksi Ternak Terapan, 2023)
Haugh unit is one of the indicators that determine albumen quality. This study aims to know the correlation and the magnitude of the effect of albumen width, albumen height, and albumen index on the haugh unit of sentul chicken eggs. The research method used was correlational method. This research was using secondary data of 119 sentul chicken eggs and tested with normality test, linearity test, correlation, and path analysis used SPSS 26. The result showed that there was a correlation between albumen width, albumen height, and albumen index on the haugh unit of sentul chicken eggs and the effect of albumen height on the haugh unit of sentul chicken eggs is 83.13% and the effect of albumen index on the haugh unit of sentul chicken eggs is 9.78%.